2017
DOI: 10.15537/smj.2017.1.16448
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of patients with burn injury treated in a burn center in Turkey during the Syrian civil war

Abstract: Objectives:To report the management of burn injuries that occured in the Syria civil war, which were referred to our burn center.Methods:Forty-three patients with burns, injured in the civil war in Syria and whom were referred to Dr. Lütfi Kırdar Kartal Educating and Training Hospital Burn Centre of İstanbul, Turkey between 2011-2015 were analyzed in a retrospective study.Results:Most of our patients were in major burn classification (93%; 40/43) and most of them had burns >15% total on body surface area. Most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
1
5
1
2
Order By: Relevance
“…In a study by Uwingabiye et al, the results were in contrast to our results so that the resistance rate was significantly higher in BICU than in wards (19). This difference can be related to environmental differences between hospitals such as the level of hygiene in ICUs and the proficiency of personnel in different wards (34). Different levels of hand hygiene and environmental disinfection can change the results.…”
Section: Discussioncontrasting
confidence: 99%
“…In a study by Uwingabiye et al, the results were in contrast to our results so that the resistance rate was significantly higher in BICU than in wards (19). This difference can be related to environmental differences between hospitals such as the level of hygiene in ICUs and the proficiency of personnel in different wards (34). Different levels of hand hygiene and environmental disinfection can change the results.…”
Section: Discussioncontrasting
confidence: 99%
“…Especially; they affect the young population and this changes the structure of the community, for example, as we have seen in burn patients, more children and young people are affected. As we have seen in the studies done, it is stated that the population migrating to other countries is mostly in the group of males (70 -100 %) and young people (16-34 years) (16)(17)(18)(19). In this study, similar data were obtained.…”
Section: Discussionsupporting
confidence: 85%
“…In total, 38 publications met the inclusion criteria of this systematic review as shown in Figure 1 10–47. There was no other systematic review on this area of research found.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 13 842 patients were reported across the 38 publications. Seven papers did not indicate the gender of the casualties 10 11 15 23 26 29 40. Eight papers met the eligibility criteria and had specific data for children aged less than 18 years 12 13 19 24 27 44–46.…”
Section: Resultsmentioning
confidence: 99%